What requeriments must be met for the Law of the Forum to apply a maintenance obligation? Case C-214/17, Mölk - Rodríguez Vázquez, María Ángeles (CUADERNOS DE DERECHO TRANSNACIONAL, 2019)
In the Judgment of 20 September 2018, in case C-214/17, Alexander Mölk c. Valentine Mölk, the Court of Justice of the European Union establishes that the law of the forum, designated under Article 4.3 of the Hague Protocol of 2007, is not that law governs a subsequent application for a reduction in the amount of maintenance lodged by the debtor against the creditor with the courts of the State where that debtor is habitually resident. The law of the forum is subject to two conditions: first, the authority seized must be that of the State of the debtor’s habitual residence and, second, the proceedings must be instituted by the creditor.
Keywords: Hague Protocol of 23 November 2007; maintenance obligations; law applicable